Roselle (Hibiscus sabdariffa L.) Tea Protects Against Alcohol-Induced Renal Toxicity by Enhancing Endogenous Antioxidant Defence in Wistar Rats - Putri Dafriani; Eliza Arman; Annita Annita (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2026)
In Indonesia, the choice between area source and smoothed seismicity approaches has been driven by data availability rather than scientific evaluation, and no systematic comparison of both methods at the national scale has been conducted. This study compared both approaches across Indonesia to evaluate their differences in PGA estimation and assess the forecasting skill of the smoothed seismicity model. Both models were applied to the same declustered earthquake catalog with a Magnitude of Completeness of 4.7, b-value of 0.89, and a-value of 8.753, using identical Ground Motion Prediction Equations within a probabilistic seismic hazard analysis framework. Both models consistently identified North Sulawesi as the highest hazard region and Kalimantan as the lowest. The smoothed seismicity model produced higher maximum PGA values of 2.13 g compared to 1.1597 g and 1.5901 g from the area source model at 10% and 2% probability of exceedance in 50 years, respectively. Molchan Diagram validation yielded an Area Skill Score of 0.88 and R-score of 0.656, confirming strong forecasting skill. The two methods are complementary, and their integration within a logic tree framework is recommended for future national-scale PSHA in Indonesia.